Preliminary data on the feeding habits of the freshwater stingrays Potamotrygon falkneri and Potamotrygon motoro (Potamotrygonidae) from the Upper Paraná River basin, Brazil - Silva, Thiago Buosi [UNESP]; Uieda, Virginia Sanches [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2007)
As raias da família Potamotrygonidae representam um grupo singular da ictiofauna Neotropical. Apesar de serem antigos os relatos sobre o grupo, ainda são muitas as questões que permanecem sem resposta, sobretudo no que diz respeito à biologia das espécies que ocorrem na Bacia do Paraná-Paraguai. No presente trabalho foi analisada a dieta de Potamotrygon falkneri e Potamotrygon motoro, capturadas no Alto Rio Paraná, a jusante da Usina Hidrelétrica Engenheiro Souza Dias (UHE Jupiá). As duas espécies de raias apresentaram dieta diversificada, ingerindo 14 itens, entre moluscos, crustáceos, insetos e peixes, porém com predominância de insetos aquáticos em diversidade e abundância. Somente um indivíduo de cada espécie ingeriu peixe. Potamotrygon motoro consumiu principalmente Ephemeroptera, enquanto P. falkneri, principalmente Mollusca, Hemiptera e Trichoptera. Os dados aparentemente indicam uma dieta mais especializada de P. motoro, com maior consumo de Ephemeroptera (Baetidae), e uma dieta mais generalizada de P. falkneri. A análise dos indivíduos capturados em três micro-hábitats, que diferem quanto ao tipo de substrato e presença de vegetação marginal, sugere diferenças nos tipos de alimentos consumidos.

Stingrays of the Potamotrygonidae family are a singular group of Neotropical ichthyofauna. Although ancient reports exist about the group, there are still many questions that need to be clarified, such as the biology of the species that occur in the Paraná-Paraguay River system. In the present work, the diet of Potamotrygon falkneri and Potamotrygon motoro, captured in the Upper Paraná River, downstream from the Engenheiro Souza Dias Hydroelectric Power Station (UHE Jupiá), was analyzed. Both species showed a diversified diet, consisting of 14 food items, including Mollusca, Crustacea, Insecta and fish, with the predominance in diversity and abundance of aquatic insects. Only one individual of each species ingested fish. Potamotrygon motoro consumed mainly Ephemeroptera, while P. falkneri consumed mainly Mollusca, Hemiptera and Trichoptera. The data apparently indicate a more specialized diet for P. motoro, consuming more Ephemeroptera (Baetidae), and a more generalized diet for P. falkneri. The analysis of individuals captured in three microhabitats that differ in function of the substrate type and presence of marginal vegetation, suggests differences in the food items consumed.
Dados preliminares sobre o hábito alimentar das raias de água doce Potamotrygon falkneri e Potamotrygon motoro (Potamotrygonidae), na Bacia do Alto Rio Paraná, Brasil
Keywords: dieta; raias; partilha de recursos; micro-hábitat; diet; rays; resource partitioning; microhabitat